The outsider : a novel - Gabhart, Ann H., 1947- (Grand Rapids, MI : Revell, 2008)
Gabrielle Hope has a special gift of "knowing" the future. When she and her mother join the Pleasant Hill Shaker community in 1807, the members embrace her ability, although it sometimes frightens quiet Gabrielle. But when one vision comes true, a chain of events and an unlikely love challenge her loyalty to this chaste community
Keywords: Shakers -- Fiction; Kentucky -- History -- 1792-1865 -- Fiction